Assessment of Land for the Cultivation of Wheat in the Northern IslandIrrigation Project Using Remote Sensing and Geographic InformationSystems - Jamal, Saleem (Iraqi Journal of Science, 2024)
The research aims to assess the suitability of Wheat cultivation in North Al-Jezira Irrigation Project Nineveh Governorate at the actual and in the potential aftermajor improvements possible. By using remote sensing to classify land use and landcover, also using geographic information systems for input and save the data tobuilding data bank of land resources and land characteristics relate to the landevaluation, also the requirements and limitations for the cultivation of Wheat in thestudy area, in the processing and building computer model for the evaluated andclassification of land suitability actual and potential for the Wheat cultivation in thestudy area, then display the results which showed that the actual land suitabilityclassification for Wheat cultivation in the study area Is S1, S1-S2 ,S2 ,S2-S1, S3,which occupies area of 44%, 17%, 35, 2%, 2% respectively for each class, it ispossible improvements and reclamation some of the limitation for the cultivation ofWheat in the future to change the land index .